Hook types influences the catch effectiveness, injuries, and survival rates of fishes in recreational fishing - Wan Morni, Wan Zabidii; Abit, Lirong Yu; Rusdi, Siti Nur Sahwati; Lee, Nicole Siao Yen (Malaysian Society of Applied Biology, 2023)
The physical damage inflicted on captured fish in recreational fishing activities tends to be influenced by hook type. Therefore, the present study aims to investigate the suitability of hook type for catching fish as well as the evaluation of injuries and survival rates after catch-and-release. The sampling was conducted at a recreational fish pond situated at Universiti Putra Malaysia Bintulu Sarawak Campus from July until November 2022. Three sets of fishing rods with two types of hooks (circle hook & octopus hook) were used in this study. The catch efficiency, injury level, and survival rates of both types of hooks were assessed. A total of 41 and 22 fish were successfully caught using circle hooks and octopus hooks, respectively. Of the total fish caught, 39 out of 41 and nine out of 22 of the fishes caught were tilapia. The hooking location (non-critical area) of octopus hooks and circle hooks on the tilapia was approximately 100% and 81.8%, respectively. A total of 15.38% of hooks are located within the critical area (gills) of tilapia when using the circle hook and none for octopus hooks. There was 100% mortality in fish hooked in the critical area, for instance, hooks pinned inside gills. This occurrence may relate to the shape of the circle hook whereby the length of the gape is shorter in comparison to the octopus hook. Now when fish ingested the bait, the hook easily entered deeper areas of the fish’s mouth, which led to severe damage. Thus the present study recommends the use of octopus hooks in recreational fishing to reduce fish mortality rate for catch and release excursions. The results obtained from this study will be useful baseline input for recreational anglers to improve C&R practices in Malaysia.